The Impact of Card-Based Learning Methods on Math Learning - Solehah, Azmiatun; Vera Mandailina; Mahsup; Abdillah; Wasim Reza (Universitas Pendidikan Ganesha, 2024)
There have been many applications of card-based learning methods in education, one of which is in mathematics lessons. However, no one has discussed more specifically the impact of card-based learning methods with many variations, such as making math, card sorting, index cards, flashcards and other cards in mathematics lessons. This research aims to analysed how card-based learning methods significantly impact mathematics learning. The methods used in this research are quantitative and meta-analysis. Data sources are research results relevant to the research topic and meet the inclusion and exclusion criteria. Data were analysed using JASP software by inputting Effect Size (ES) and Standard Error (SE) values. The data collection method uses a literature study. The cumulative data analysis of the card-based learning method showed many variations in mathematics learning, totalling 68%. The analysis results based on the type of card that has the highest influence on mathematics learning is card sort, with a percentage of 73% in the medium category. These results show that the card-based method significantly impacts mathematics learning. So, the results of this research can be used as a reference for applying card-based methods in mathematics lessons.